2022
DOI: 10.1097/cm9.0000000000002172
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of urticaria in China: a population-based study

Abstract: Background: Urticaria is a common skin disease characterized by episodes of wheals, and it has a negative effect on patients' quality of life. Large-scale population-based epidemiological studies of urticaria are scarce in China. The aim of this survey was to determine the prevalence, clinical forms, and risk factors of urticaria in the Chinese population. Methods: This survey was conducted in 35 cities from 31 provinces, autonomous regions, and municipalities of China. Two to three communities in each city we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…A considerably higher proportion of these patients showed a relatively high D‐dimer level, which was nearly six times higher than that in the normal group. Moreover, the number of female patients exceeded half of the number of included patients, which is similar to previous studies and may be associated with sex hormones 17,18 . This result indicates that severe AU might be associated with a high D‐dimer level, which means that the coagulation system of patients with severe AU appears more active than assumed.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A considerably higher proportion of these patients showed a relatively high D‐dimer level, which was nearly six times higher than that in the normal group. Moreover, the number of female patients exceeded half of the number of included patients, which is similar to previous studies and may be associated with sex hormones 17,18 . This result indicates that severe AU might be associated with a high D‐dimer level, which means that the coagulation system of patients with severe AU appears more active than assumed.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the number of female patients exceeded half of the number of included patients, which is similar to previous studies and may be associated with sex hormones. 17,18 This result indicates that severe AU might be associated with a high D-dimer level, which means that the coagulation system of patients with severe AU appears more active than assumed. According to our clinical observation, the level of D-dimer drops as symptoms improve after appropriate treatments, similar to the findings of a recent study.…”
Section: Discussionmentioning
confidence: 84%
“…Among them, up to 45% of patients will progress to chronic urticaria, which is characterized by complex pathogenesis, reduced quality of life and high health care costs ( 3 ). Although two recent population-based epidemiological studies of urticaria in China reported a lifetime prevalence of urticaria of 7.30% ( 4 ) and an estimated prevalence of chronic urticaria of 2.6% ( 5 ), the actual prevalence of urticaria may be greatly underestimated given the low medical help-seeking behavior and insufficient service utilization of most urticaria patients ( 6 , 7 ). Previous studies have shown that 76.9% of adults use the internet for health purposes ( 8 ), and many patients tend to use internet searches to seek for initial diagnosis and health advice/solutions.…”
Section: Introductionmentioning
confidence: 99%
“…9 Various factors, such as urban living, exposure to pollutants, anxiety, depression, thyroid disorders, Helicobacter pylori infection and a personal or family history of allergies, have been linked to a higher prevalence of CU. 9 In addition, research has shown associations between CU and metabolic disorders, highlighting the importance of exploring various metabolic pathways, including proinflammatory pathway, oxidative stress and activation of the coagulation system to determine new treatment targets. While omalizumab has shown effectiveness for some patients with inadequate response to antihistamines, there are still patients with autoimmunerelated CU who do not respond well to this treatment.…”
mentioning
confidence: 99%
“…Chronic urticaria (CU) is another common allergic skin disease in China that significantly impacts patients' daily life, presenting a considerable public health challenge. Recent data revealed that the lifetime prevalence of urticaria in China is 7.93%, with a point prevalence of 0.76% 9 . Various factors, such as urban living, exposure to pollutants, anxiety, depression, thyroid disorders, Helicobacter pylori infection and a personal or family history of allergies, have been linked to a higher prevalence of CU 9 .…”
mentioning
confidence: 99%